Which subjective factors determine the self-rated negative occupational prognosis of patients in cardiac rehabilitation? A qualitative study. (11th May 2022) - Brehmer, N; Wolff, L L; Voeller, H; Salzwedel, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: A negative self-rated occupational prognosis hinders the vocational reintegration of patients after cardiac rehabilitation (CR). Several studies reveal that these patients often show reduced physical performance as well as higher psychosocial burden. Although the current evidence indicates that self-rated (negative) occupational prognosis of the patients in CR is a multi-factorial issue, there are no studies on subjective factors determining that prognosis. Purpose: The aim of this study was to understand what subjective factors determine a self-rated negative occupational prognosis of patients in CR. Methods: A single-centre qualitative study using thematic analysis was conducted in the fourth quarter of 2021. Data was collected by two researchers using in-depth interviews with 20 patients with self-rated negative occupational prognosis and 5 patients with non-impaired prognosis. We interviewed working-age patients (range 18-60 years) who were admitted to a rehabilitation program usually within 14 days after an acute cardiac event. The participants were selected by theoretical sampling. All interviews were recorded, transcribed and coded. We concluded the codes in main themes. Results: In our analysis of interview texts we extrapolated seven themes: 1) environmental factors (social support, requalification opportunities, industry-specific occupational risks); 2) personal factors (professional skills, knowledge about own impairments, attitude toward future); 3) factors that occurred before a cardiac event (previous illness, unhealthy lifestyle, familial predisposition to disease); 4) factors that occurred after a cardiac event (health stigma and discrimination, disabilities, changed personal priorities); 5) patient's health perception including physical capacity; 6) possibilities to change the working conditions; 7) heart-focused anxiety. The themes 1 to 4 can be considered as an umbrella term for multiple individual factors. However, the themes 5 to 7, which indicate specific determining subjective factors for self-rated occupational prognosis, appeared in most of the interviews. Conclusion: We conclude that the self-rated occupational prognosis is determined by a complex set of individual factors. However, three themes – patient´s health perception, opportunity to adjust work place, and resilience towards heart-focused anxiety- were mentioned by the majority of patients regarding their self-accessed occupational prognosis. Affected patients are likely to require a multidisciplinary rehabilitation program, whereas these three themes might be addressed by social workers and psychologists.